Being Old And Being A Woman: A Research On The Age And Gender Relationship In The Award-Winning Actors And Actresses Of The Turkish Cinema - Oktuğ Zengin, Melis (The Turkish Online Journal of Design Art and Communication, 2014)
According to the World Health Organization data, proportion of elderly individuals to total population is going to exceed that of children and youth in about 50 years. In the aging population, proportion of females is higher than the proportion of males. Researches show that women are to face numerous problems resulting from discriminatory practices based on age besides gender pattern in social and economic life. In this study, the discriminatory practices that the aging female population was exposed to in professional life were addressed within the cinema sector. Sample of the research consists of actors and actresses who have received awards in the branches of best actress, best actor, best supporting actress and best supporting actor in the longest-running film festival of Turkey, Antalya Golden Orange Film Festival, since the beginning of the festival. Receiving an award is an indicator of successful performance for cinema actors and actresses. In this context, the role of age and gender in professional careers of cinema actors and actresses was investigated by descriptive statistics method, on the basis of age distribution with respect to the gender of cinema actors and actresses who have received awards in best actress, best actor, best supporting actress and best supporting actor since the beginning of Antalya Golden Orange Film Festival.Results obtained from the study revealed similarities to researches related to actresses in the American Cinema which is a part of the literature. Research findings show that the mean age of award-winning actors is higher than the mean age of award-winning actresses in all the branches under consideration and that women receive awards at younger ages compared to men. In this context, it can be suggested that sexist approaches give rise to double jeopardy for actresses in advanced age and their professional careers are constricted in their old age.
Keywords: Discrimination; Age Discrimination; Cinema; Ayrımcılık; Yaş Ayrımcılığı; Sinema